Analisis dan Perancangan Sistem Informasi Rapat Online FMIPA UNTAN menggunakan UML - Renny Puspita Sari; Istikoma Istikoma (Ikatan Ahli Informatika Indonesia, 2018)
Meetings are routine activities held mainly on the scope of educational institutions, one of the Faculty of Mathematics and Natural Sciences (FMIPA). Although FMIPA UNTAN began to focus on the development of technology. However, not all things done by applying the concept of information technology, there are still activities that are done conventionally one of them is the meeting activities. Conventional meeting involves obstacles such as improper invitation letter invitation notification, so that the participants of invited meetings are uninformed and do not attend the meeting. In addition, the changing meeting schedule is not in accordance with the invitation of the meeting, Another obstacle is the attendance attendance list of meeting participants and minutes of meetings can not be well documented. By looking at the many problems that arise in the implementation of conventional meeting activities can lead to the main objectives of meeting activities can not be achieved properly. Therefore, to overcome the problem requires an alternative solution model of communication that does not depend on the location, distance or time of the meeting. One alternative model of communication is by designing online based meetings application website using UML diagrams (Unified Modeling Language). The design of this online meeting is expected to facilitate the distribution of invitation information directly to the members of the meeting concerned. Meeting participants can enter into the application to find out the meeting agenda that will take place and find out the documentation of the meeting result written by the minutes of the meeting after the end of the meeting.